High-strength anti-aging PE film, preparation method and application
By introducing high-performance antioxidants and amphiphilic modified inorganic composite materials into the PE film, combining nano calcium fluoride and hydrophobic fluorine-containing chains, the problem of insufficient thermal aging performance of polyethylene film at high temperatures is solved, and high Transparency and excellent mechanical properties.
Patent Information
- Application Number
- CN202411834830.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyethylene films have insufficient heat-resistant aging performance and mechanical strength in high temperature environments, and the addition of fillers will affect the transparency, making it difficult to meet the needs of the ultraviolet cured CIPP lining repair process.
By introducing high-performance antioxidants and amphiphilic modified inorganic composite materials into the PE film, modifying polyethylene, combining nano calcium fluoride and hydrophobic fluorine-containing chains, the mechanical properties, thermal aging resistance and transparency of the PE film are improved.
It achieves excellent performance of PE film under high temperature conditions, maintains high transparency and good anti-slip performance, and significantly improves mechanical strength and heat-resistant aging ability.
Smart Images

Figure CN119320506A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a high-strength aging-resistant PE film, a preparation method and application thereof. Background Art
[0002] As one of the CIPP repair processes, the UV-curing CIPP lining repair process is to pull the glass fiber hose pre-impregnated with resin into the pipe to be repaired, and complete the repair of the old building lining after curing with ultraviolet light, eliminating the steps of scaffolding, turning, and water use, and achieving efficient, environmentally friendly, economical, and 100% non-excavation repair. The UV-curing hose materials include high-temperature resistant and non-slip inner membrane, resin-rich wear-resistant layer, corrosion-resistant glass fiber fabric reinforcement layer, one-way breathable and anti-seepage layer, and high puncture and UV protection film. Among them, the high-temperature resistant and non-slip inner membrane, as a carrier of air pressure, must have high strength to make the material fully stretch and fit the original pipe wall, and ensure that it is not blown apart by air pressure. The inner membrane material on the market is generally polyethylene film, but the polyethylene film has poor temperature resistance and weak heat aging resistance (the operating temperature of polyethylene film under normal circumstances cannot exceed 80 degrees), and the construction temperature of the UV-curing CIPP lining repair process is often above 100°C.
[0003] In the prior art, the mechanical strength and heat aging resistance of polyethylene films are generally improved by adding fillers. However, the addition of fillers (especially inorganic fillers) often leads to a decrease in the transparency of the polyethylene film. In order to ensure that UV light can penetrate the inner film to solidify the resin material, the inner film must have high transparency. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a high-strength aging-resistant PE film, comprising the following steps: Step (1), preparing POSS-SH by (3-mercaptopropyl)trimethoxysilane; then modifying POSS-SH by allyl glycidyl ether to obtain modified POSS; Step (2), 3,5-di-tert-butyl-2-hydroxybenzaldehyde reacts with p-phenylenediamine to obtain an intermediate product; the intermediate product is combined with modified POSS to obtain a high-performance antioxidant; Step (3), dry-modifying the calcium sulfate whiskers with 3-aminopropyltriethoxysilane to obtain surface-modified calcium sulfate whiskers; using glutaraldehyde as a crosslinking agent, grafting 3,5-diaminobenzoic acid onto the surface-modified calcium sulfate whiskers to obtain functionalized calcium sulfate whiskers; depositing nano-calcium fluoride on the functionalized calcium sulfate whiskers to obtain an inorganic composite material; The inorganic composite material is modified by 3-glycidyloxypropyltrimethoxysilane to obtain a surface-modified inorganic composite material; a fluorine-containing compound and polyethyleneimine are grafted onto the surface-modified inorganic composite material to obtain an amphiphilic modified inorganic composite material; Step (4), mixing the amphiphilic modified inorganic composite material, the high-performance antioxidant, and the modified polyethylene, melt blending, and blowing the film to obtain a high-strength and aging-resistant PE film; The preparation method of modified polyethylene comprises the following steps: Step S1, grafting maleic anhydride onto low-density polyethylene using a solvothermal method to obtain maleic anhydride grafted polyethylene; Step S2, reacting maleic anhydride grafted polyethylene with mercaptoethylamine to obtain functionalized polyethylene; Step S3: reacting the functionalized polyethylene with 1,2-epoxy-5-hexene to obtain modified polyethylene.
[0005] Preferably, in step (1), the preparation method of the modified POSS is: Mercaptopropyltrimethoxysilane, a 37wt% aqueous solution of hydrochloric acid and ethanol are mixed, stirred and reacted at 85-95°C for 20-30h, centrifuged to obtain a white precipitate, dissolved the white precipitate with tetrahydrofuran and precipitated with acetonitrile at 2-5°C, purified to obtain POSS-SH; wherein the mass ratio of mercaptopropyltrimethoxysilane, the aqueous solution of hydrochloric acid and ethanol is (8-16):(17.8-35.6):(144-288); Mix allyl glycidyl ether, POSS-SH and tetrahydrofuran, stir and react at room temperature for 3.5-4.5h, and purify after the reaction to obtain modified POSS; wherein the mass ratio of allyl glycidyl ether, POSS-SH and tetrahydrofuran is (3-5):(6-10):(100-120); In the above process, thiolated polyhedral oligomeric silsesquioxane (i.e., POSS-SH) is prepared by hydrolysis of (3-mercaptopropyl)trimethoxysilane, and the thiol groups in POSS-SH undergo a thiol-ene click reaction with the carbon-carbon double bonds of allyl glycidyl ether to convert the thiol groups in POSS-SH into epoxy groups.
[0006] Preferably, in step (2), the preparation method of the high performance antioxidant is: 3,5-di-tert-butyl-2-hydroxybenzaldehyde and ethanol were mixed at a mass ratio of (11.7-23.4):(120-200) The mixture is mixed in a mass ratio of (6-12):(80-150):(12.2-24.3) to obtain a solution A; p-phenylenediamine, ethanol, and a 23wt% potassium hydroxide aqueous solution are mixed in a mass ratio of (6-12):(80-150):(12.2-24.3) to obtain a solution B; the solution B is added dropwise to the solution A at a rate of 0.5-1mL / min, reacted at 55-65°C for 4.5-5.5h, cooled, transferred to an ice water bath, sodium borohydride is added, and reacted for 1.5-2.5h. After the reaction is completed, the pH is adjusted to 4.8-5.2 with a 36wt% hydrochloric acid aqueous solution, and purified to obtain an intermediate product; wherein the mass ratio of 3,5-di-tert-butyl-2-hydroxybenzaldehyde, p-phenylenediamine, and sodium borohydride is (11.7-23.4):(6-12):(2.3-4.5); The intermediate product is added to ethanol, stirred for 20-40 minutes, and then the modified POSS is added, heated to 70-75°C, and the stirring reaction is continued for 20-28 hours. After the reaction is completed, the solvent is evaporated to obtain a high-performance antioxidant; wherein the mass ratio of the intermediate product, ethanol, and modified POSS is (8-12):(100-150):(110-20); In the above process, the amino group at one end of p-phenylenediamine reacts with the aldehyde group of 3,5-di-tert-butyl-2-hydroxybenzaldehyde to obtain an intermediate product containing hindered phenol and secondary amine groups; further, the amino group in the intermediate product reacts with the epoxy group in the modified POSS through a ring-opening reaction, and the POSS with a cage structure is combined with the intermediate product to obtain a high-performance antioxidant.
[0007] Preferably, in step (3), the preparation method of the functionalized calcium sulfate whiskers is: The calcium sulfate whisker is pre-dried at 50-60° C. for 2-3 hours, heated to 95-105° C., and the stirring speed is adjusted to 900-1100 r / min, and then 3-aminopropyltriethoxysilane is added, and the stirring and mixing is continued for 10-20 minutes, and cooled to obtain surface-modified calcium sulfate whisker; wherein the mass ratio of 3-aminopropyltriethoxysilane to calcium sulfate whisker is 100:(2-5); The surface-modified calcium sulfate whisker, glutaraldehyde and N,N-dimethylformamide are mixed, reacted at 95-105° C. for 9-11 hours, and purified to obtain grafted modified calcium sulfate whisker; wherein the mass ratio of the surface-modified calcium sulfate whisker, glutaraldehyde and N,N-dimethylformamide is (5.7-11.4):(6.5-12.5):(150-200); Dissolve 3,5-diaminobenzoic acid in ethanol, add grafted modified calcium sulfate whiskers, stir and react at 45-55°C for 10-14 hours, purify, and obtain functionalized calcium sulfate whiskers, wherein the mass ratio of 3,5-diaminobenzoic acid, ethanol, and grafted modified calcium sulfate whiskers is (8.5-12.5):(120-150):(10-15).
[0008] Preferably, in step (3), the method for preparing the inorganic composite material is: Add functionalized calcium sulfate whiskers to deionized water, perform ultrasonic treatment for 30-60 minutes, then add ammonium fluoride, stir at room temperature for 10-20 minutes, then dropwise add a 28.6wt% calcium chloride aqueous solution within 20-40 minutes, continue stirring for 50-70 minutes, purify, and obtain an inorganic composite material; wherein the amount ratio of the functionalized calcium sulfate whiskers, deionized water, ammonium fluoride, and calcium chloride aqueous solution is (10-12) g:(60-80) g:(6-12) g:(20-40) mL; In the above process, the calcium sulfate whisker is dry-modified by 3-aminopropyltriethoxysilane, and amino groups are introduced on the surface of the calcium sulfate whisker. Then, glutaraldehyde is used as a cross-linking agent, and the aldehyde group of glutaraldehyde reacts with the amino group of the surface-modified calcium sulfate whisker and the amino group of 3,5-diaminobenzoic acid, so that a large number of amino groups and carboxyl groups are introduced on the surface of the calcium sulfate whisker. The carboxyl group and the amino group can effectively combine with the calcium fluoride generated by the reaction of ammonium fluoride and calcium chloride through hydrogen bond interaction, so that nano calcium fluoride is deposited on the surface of the calcium sulfate whisker, thereby forming an inorganic composite material.
[0009] Preferably, in step (3), the preparation method of the amphiphilic modified inorganic composite material is: Ammonia water, deionized water and ethanol with a mass fraction of 25wt% are mixed in a volume ratio of 0.7:10:30 to obtain a mixed solution; an inorganic composite material is added to the mixed solution, ultrasonically treated for 50-80min, and then 3-glycidyloxypropyltrimethoxysilane and ethanol are added, and stirred at 55-65°C for 100-150min. After the reaction is completed, purification is performed to obtain a surface-modified inorganic composite material; wherein the mass ratio of the mixed solution, the inorganic composite material, 3-glycidyloxypropyltrimethoxysilane and ethanol is (34.6-69.2):(5-10):(0.2-0.5):(8-16); In a nitrogen atmosphere, perfluorooctanoyl chloride is added to tetrahydrofuran, stirred for 20-40 minutes, and then 1,3-propylenediamine is added, and the reaction is stirred at room temperature for 10-15 hours, and then a sodium hydroxide aqueous solution with a concentration of 0.04 g / mL is added, and the stirring is continued for 40-60 minutes, and the fluorine-containing compound is obtained; wherein the amount ratio of perfluorooctanoyl chloride, tetrahydrofuran, 1,3-propylenediamine, and sodium hydroxide aqueous solution is (4.3-8.6) g: (80-100) g: (0.7-1.4) g: (10-20) mL; The surface-modified inorganic composite material is added to N,N-dimethylformamide, subjected to ultrasonic treatment for 20-40 minutes, and then a fluorine-containing compound and a polyethyleneimine aqueous solution are added, heated to 70-75° C., stirred for reaction for 20-28 hours, and after the reaction is completed, purified to obtain an amphiphilic modified inorganic composite material; wherein the mass ratio of the surface-modified inorganic composite material, N,N-dimethylformamide, the fluorine-containing compound, and the polyethyleneimine aqueous solution is (5-7):(80-120):(1.8-3.4):(8-16); In the above process, the silanol after hydrolysis of 3-glycidyloxypropyltrimethoxysilane reacts with the inorganic composite material, and an epoxy group is introduced on the surface of the inorganic composite material to obtain a surface-modified inorganic composite material; the acyl chloride group of perfluorooctanoyl chloride reacts with the amino group at one end of 1,3-propylenediamine to obtain a fluorine-containing compound containing a hydrophobic chain; further, the epoxy group in the surface-modified inorganic composite material is ring-opened and reacts with the amino group in the fluorine-containing compound and polyethyleneimine, and a hydrophobic fluorine-containing chain and a hydrophilic polyethyleneimine chain are introduced on the surface of the inorganic composite material, so that the inorganic composite material has amphiphilic properties.
[0010] Preferably, in step (4), the mass ratio of the amphiphilic modified inorganic composite material, the high-performance antioxidant and the modified polyethylene is (3.2-4.8):(12-20):100; the melt blending conditions are: first melt blending at 160-170°C at a rotation speed of 15-25 r / min for 2-5 min, and then melt blending at a rotation speed of 40-60 r / min for 5-8 min.
[0011] Preferably, in step (4), the thickness of the high-strength aging-resistant PE film is 0.3-0.5 mm.
[0012] Furthermore, in step (4), the preparation method of the modified polyethylene is: Step S1, mixing low-density polyethylene, maleic anhydride, dicumyl peroxide, and toluene, heating to 140-160° C. and maintaining for 4.5-5.5 hours in a sealed environment, naturally cooling to room temperature, and purifying to obtain maleic anhydride-grafted polyethylene; wherein the mass ratio of low-density polyethylene, maleic anhydride, dicumyl peroxide, and toluene is (5-10):(0.5-1.2):(0.4-0.6):(40-60); Step S2, in a nitrogen atmosphere, adding maleic anhydride grafted polyethylene to N,N-dimethylformamide, stirring for 20-40 minutes, then adding mercaptoethylamine, reacting at 55-65° C. for 5.5-6.5 hours in a nitrogen atmosphere, purifying, and obtaining functionalized polyethylene; wherein the mass ratio of maleic anhydride grafted polyethylene, N,N-dimethylformamide, and mercaptoethylamine is (6-10):(80-100):(0.8-1.2); Step S3, adding the functionalized polyethylene to N,N-dimethylformamide, stirring for 20-40 minutes, then adding 1,2-epoxy-5-hexene, stirring and reacting at room temperature for 5-7 hours, purifying, and obtaining modified polyethylene; wherein the mass ratio of the functionalized polyethylene, N,N-dimethylformamide, and 1,2-epoxy-5-hexene is (6-10):(80-100):(1.1-1.8); In the above process, dicumyl peroxide is used as an initiator and toluene is used as a solvent. The solvothermal method is used to graft copolymerize maleic anhydride onto low-density polyethylene to introduce side chains to obtain maleic anhydride grafted polyethylene; the maleic anhydride group in the maleic anhydride grafted polyethylene is ring-opened and then reacts with the amino group of mercaptoethylamine to obtain a functionalized polyethylene whose side chains contain thiol, amide and carboxyl groups; the thiol group of the functionalized polyethylene reacts with the double bond of 1,2-epoxy-5-hexene to introduce epoxy groups on the polyethylene side chains.
[0013] The invention discloses a high-strength aging-resistant PE film prepared by adopting the preparation method of the high-strength aging-resistant PE film.
[0014] An application of the high-strength and aging-resistant PE film as described above in an ultraviolet-cured hose inner membrane material.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention improves the heat-oxidative aging resistance and mechanical properties of the PE film by adding a high-performance antioxidant in the PE film. The high-performance antioxidant is obtained by combining an intermediate product with a modified POSS with a covalent bond. The intermediate product contains a hindered phenol and a secondary amine group, and the secondary amine is very close to the phenolic hydroxyl group. On the one hand, it is conducive to the formation of intramolecular hydrogen bonds, and improves the thermal stability of the PE film. On the other hand, the phenolic hydroxyl group can contribute hydrogen atoms to the secondary amine free radical, and the two have a stronger ability to capture active free radicals in collaboration, and play a collaborative heat-resistant aging effect; and in the modified POSS, due to its own unique cage-shaped organic-inorganic hybrid structure, high molecular weight and high thermal stability, the mechanical properties and heat-resistant aging properties of the PE film can be improved; The intermediate product is combined with the modified POSS, and the compatibility of POSS with a polyethylene matrix can also be improved. In addition, the high-performance antioxidant with a high molecular weight has better migration resistance and anti-volatility, even under high temperature conditions, excellent heat-resistant aging ability can also be brought into play, so that the high-strength anti-aging PE film of the present invention can still maintain excellent performance when working at high temperatures.
[0016] 2. The amphiphilic modified inorganic composite material of the present invention is obtained by depositing nano calcium fluoride on the surface of calcium sulfate whisker and then grafting hydrophobic fluorine-containing chains and hydrophilic polyethyleneimine chains, wherein: the calcium sulfate whisker is used as a reinforcing filler and a nucleating agent to improve the mechanical properties and thermal stability of the PE film, and to improve the transparency by reducing the crystallinity of low-density polyethylene; the introduction of a large number of amino groups and carboxyl groups on the surface of the calcium sulfate whisker is conducive to the deposition of nano calcium fluoride, the deposition of nano calcium fluoride enhances the roughness of the surface of the calcium sulfate whisker, and the surface effect of the nano calcium fluoride can improve the compatibility of the calcium sulfate whisker with polyethylene, and the most important thing is that the refractive index between the nano calcium fluoride and the polyethylene is similar, so that the PE film can maintain high transparency and a certain roughness; further, the introduction of the hydrophobic fluorine-containing chain and the hydrophilic polyethyleneimine chain in the amphiphilic modified inorganic composite material further improves the compatibility of the inorganic composite material with polyethylene, and makes the PE film amphiphilic, has good bonding to the dry and wet interfaces, and exhibits anti-slip performance. Therefore, the addition of the amphiphilic modified inorganic composite material of the present invention can endow the PE film with better mechanical properties, heat aging resistance, transparency and anti-slip properties.
[0017] 3. The present invention modifies low-density polyethylene and uses it as the substrate of the PE film. Side chains containing epoxy groups, amide groups and carboxyl groups are introduced into the modified polyethylene. The epoxy groups react with the amino groups in the amphiphilic modified inorganic composite material through a ring-opening reaction, while the amide groups and carboxyl groups can combine with the high-performance antioxidant through hydrogen bonds, thereby increasing the cross-linking density of the system and improving the dispersibility of the amphiphilic modified inorganic composite material and the high-performance antioxidant, thereby improving the performance of the PE film. In addition, since the length of the side chains of the modified polyethylene is very short, it has little effect on the mechanical strength of the PE film. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a process flow chart of the preparation method of the high-strength aging-resistant PE film of the present invention; Figure 2 It is a schematic diagram of the synthesis of the intermediate product of the present invention; Figure 3 It is a comparison chart of tensile strength test of high-strength aging-resistant PE films prepared in Examples 2-4 of the present invention and Comparative Examples 1-6; Figure 4 It is a comparison chart of the tensile strength retention rate test of the high-strength aging-resistant PE films prepared in Examples 2-4 of the present invention and Comparative Examples 1-6; Figure 5 It is a comparison chart of light transmittance test of high-strength aging-resistant PE films prepared by Examples 2-4 of the present invention and Comparative Examples 1-6. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] Example 1: This example discloses a method for preparing modified polyethylene, comprising the following steps: Step S1, 7.5 g of low-density polyethylene, 0.9 g of maleic anhydride, 0.5 g of diisopropylbenzene peroxide, and 50 g of toluene are mixed, heated to 150° C. and maintained for 5 h in a sealed environment, naturally cooled to room temperature, filtered, and the obtained product is washed with ethanol and vacuum dried at 75° C. to obtain maleic anhydride grafted polyethylene; Step S2, in a nitrogen atmosphere, add 8 g of maleic anhydride grafted polyethylene to 90 g of N,N-dimethylformamide, stir for 30 min, then add 1 g of mercaptoethylamine, react in a 60° C. oil bath in a nitrogen atmosphere for 6 h, filter, wash, and dry to obtain functionalized polyethylene; Step S3, adding 8 g of functionalized polyethylene to 90 g of N,N-dimethylformamide, stirring for 30 min, then adding 1.5 g of 1,2-epoxy-5-hexene, stirring and reacting at room temperature for 6 h, filtering, washing, and drying to obtain modified polyethylene.
[0021] Embodiment 2: This embodiment discloses a method for preparing a high-strength aging-resistant PE film, comprising the following steps: Step (1), 8 g of mercaptopropyltrimethoxysilane, 17.8 g of a 37 wt% aqueous solution of hydrochloric acid, and 144 g of ethanol were mixed, stirred at 85° C. for 30 h, and centrifuged to obtain a white precipitate, the white precipitate was dissolved in tetrahydrofuran and precipitated with 2° C. acetonitrile, filtered, washed, and dried to obtain POSS-SH; 3 g of allyl glycidyl ether, 6 g of POSS-SH, and 100 g of tetrahydrofuran were mixed and stirred at room temperature for 3.5 h. After the reaction was completed, the solvent and excess allyl glycidyl ether were removed by rotary evaporation at 80 ° C to obtain modified POSS; Step (2), dissolving 11.7 g of 3,5-di-tert-butyl-2-hydroxybenzaldehyde in 120 g of ethanol to obtain solution A; dissolving 6 g of p-phenylenediamine in 80 g of ethanol, and then adding 12.2 g of a 23 wt % potassium hydroxide aqueous solution to obtain solution B; adding solution B dropwise to solution A at a rate of 0.5 mL / min, reacting at 55° C. for 5.5 h, cooling, transferring to an ice water bath, adding 2.3 g of sodium borohydride, reacting for 1.5 h, and adjusting the pH to 4.8 with a 36 wt % hydrochloric acid aqueous solution after the reaction is completed, filtering, washing the filter residue with 50° C. hot water and toluene, and drying to obtain an intermediate product; 8 g of the intermediate product was added to 100 g of ethanol, stirred for 20 min, and then 10 g of modified POSS was added, heated to 70 ° C, and stirred for 28 h. After the reaction was completed, the solvent was evaporated to obtain a high-performance antioxidant; Step (3), pre-drying the calcium sulfate whisker at 50° C. for 3 h, adding the mixture into a reaction vessel, heating the mixture to 95° C., adjusting the stirring speed to 900 r / min, and then adding 3-aminopropyltriethoxysilane, continuing to stir and mix for 20 min, and cooling the mixture to obtain surface-modified calcium sulfate whisker; wherein the mass ratio of 3-aminopropyltriethoxysilane to calcium sulfate whisker is 100:2; 5.7 g of surface-modified calcium sulfate whiskers, 6.5 g of glutaraldehyde, and 150 g of N,N-dimethylformamide were mixed, reacted at 95° C. for 11 h, filtered, washed, and dried to obtain graft-modified calcium sulfate whiskers; 8.5 g of 3,5-diaminobenzoic acid was dissolved in 120 g of ethanol, and 10 g of grafted modified calcium sulfate whiskers were added, and the mixture was stirred at 45° C. for 14 h, and then filtered, washed, and dried to obtain functionalized calcium sulfate whiskers; 10 g of functionalized calcium sulfate whiskers were added to 60 g of deionized water, and ultrasonically treated for 30 min. Then, 6 g of ammonium fluoride was added, and stirred at room temperature for 10 min. Then, 20 mL of a 28.6 wt% calcium chloride aqueous solution was added dropwise within 20 min. The mixture was stirred for 50 min, filtered, and the residue was washed with deionized water and ethanol, and dried at 50 ° C for 8 h to obtain an inorganic composite material. Ammonia water, deionized water and ethanol with a mass fraction of 25wt% were mixed in a volume ratio of 0.7:10:30 to obtain a mixed solution; 5g of the inorganic composite material was added to 34.6g of the mixed solution, and ultrasonic treatment was performed for 50min, and then 0.2g of 3-glycidyloxypropyltrimethoxysilane and 8g of ethanol were added, and the mixture was stirred and reacted at 55°C for 150min. After the reaction was completed, the mixture was filtered, washed and dried to obtain a surface-modified inorganic composite material; In a nitrogen atmosphere, 4.3 g of perfluorooctanoyl chloride was added to 80 g of tetrahydrofuran, and stirred for 20 min. Then, 0.7 g of 1,3-propylenediamine was added, and the mixture was stirred for 10 h at room temperature. Then, 10 mL of a 0.04 g / mL sodium hydroxide aqueous solution was added, and the mixture was stirred for 40 min. The mixture was filtered, washed, and dried to obtain a fluorine-containing compound. 5 g of the surface-modified inorganic composite material was added to 80 g of N,N-dimethylformamide, and ultrasonically treated for 20 min. Then, 1.8 g of a fluorine-containing compound and 8 g of a polyethyleneimine aqueous solution were added, and the mixture was heated to 70° C. and stirred for reaction for 20 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain an amphiphilic-modified inorganic composite material. Step (4), mixing the amphiphilic modified inorganic composite material, the high-performance antioxidant, and the modified polyethylene in a mass ratio of 3.2:12:100, melt blending, and film blowing to obtain a high-strength, aging-resistant PE film with a thickness of 0.3 mm, wherein the melt blending conditions are: first melt blending at 160° C. at a rotation speed of 15 r / min for 5 min, and then melt blending at a rotation speed of 40 r / min for 8 min.
[0022] Embodiment 3: This embodiment discloses a method for preparing a high-strength aging-resistant PE film, comprising the following steps: Step (1), 16 g of mercaptopropyltrimethoxysilane, 35.6 g of a 37 wt% aqueous solution of hydrochloric acid, and 288 g of ethanol were mixed, stirred at 95° C. for 20 h, and centrifuged to obtain a white precipitate, the white precipitate was dissolved in tetrahydrofuran and precipitated with 5° C. acetonitrile, filtered, washed, and dried to obtain POSS-SH; 5 g of allyl glycidyl ether, 10 g of POSS-SH, and 120 g of tetrahydrofuran were mixed and stirred at room temperature for 4.5 h. After the reaction was completed, the solvent and excess allyl glycidyl ether were removed by rotary evaporation at 90 ° C to obtain modified POSS; Step (2), dissolving 23.4 g of 3,5-di-tert-butyl-2-hydroxybenzaldehyde in 200 g of ethanol to obtain solution A; dissolving 12 g of p-phenylenediamine in 150 g of ethanol, and then adding 24.3 g of a 23 wt % potassium hydroxide aqueous solution to obtain solution B; adding solution B dropwise to solution A at a rate of 1 mL / min, reacting at 65° C. for 4.5 h, cooling, transferring to an ice water bath, adding 4.5 g of sodium borohydride, reacting for 1.5 h, and after the reaction, adjusting the pH to 5.2 with a 36 wt % hydrochloric acid aqueous solution, filtering, washing the filter residue with 50° C. hot water and toluene, and drying to obtain an intermediate product; 12 g of the intermediate product was added to 150 g of ethanol, stirred for 40 min, and then 20 g of modified POSS was added, heated to 75 ° C, and stirred for 20 h. After the reaction was completed, the solvent was evaporated to obtain a high-performance antioxidant; Step (3), pre-drying the calcium sulfate whisker at 60° C. for 2 h, adding the mixture into a reaction vessel, heating the mixture to 105° C., adjusting the stirring speed to 900 r / min, and then adding 3-aminopropyltriethoxysilane, stirring and mixing the mixture for 20 min, and cooling the mixture to obtain surface-modified calcium sulfate whisker; wherein the mass ratio of 3-aminopropyltriethoxysilane to calcium sulfate whisker is 100:5; 11.4 g of surface-modified calcium sulfate whiskers, 12.5 g of glutaraldehyde, and 200 g of N,N-dimethylformamide were mixed, reacted at 105° C. for 9 h, filtered, washed, and dried to obtain graft-modified calcium sulfate whiskers; 12.5 g of 3,5-diaminobenzoic acid was dissolved in 120 g of ethanol, and 15 g of grafted modified calcium sulfate whiskers were added, and the mixture was stirred at 55° C. for 10 h, filtered, washed, and dried to obtain functionalized calcium sulfate whiskers; 12 g of functionalized calcium sulfate whiskers were added to 80 g of deionized water, and ultrasonically treated for 60 min. 12 g of ammonium fluoride was then added, and stirred at room temperature for 20 min. Then, 20 mL of a 28.6 wt% calcium chloride aqueous solution was added dropwise within 40 min, and stirring was continued for 70 min. The mixture was filtered, and the residue was washed with deionized water and ethanol, and dried at 70 ° C for 6 h to obtain an inorganic composite material. Ammonia water, deionized water and ethanol with a mass fraction of 25wt% are mixed in a volume ratio of 0.7:10:30 to obtain a mixed solution; 10g of the inorganic composite material is added to 69.2g of the mixed solution, and ultrasonic treatment is performed for 80min, and then 0.5g of 3-glycidyloxypropyltrimethoxysilane and 16g of ethanol are added, and the mixture is stirred and reacted at 65°C for 100min. After the reaction is completed, the mixture is filtered, washed and dried to obtain a surface-modified inorganic composite material; In a nitrogen atmosphere, add 8.6 g of perfluorooctanoyl chloride to 100 g of tetrahydrofuran, stir for 40 min, then add 1.4 g of 1,3-propylenediamine, stir and react at room temperature for 15 h, then add 20 mL of 0.04 g / mL sodium hydroxide aqueous solution, continue stirring for 60 min, filter, wash, and dry to obtain a fluorine-containing compound; 7 g of the surface-modified inorganic composite material was added to 120 g of N,N-dimethylformamide, and ultrasonically treated for 40 min. Then, 3.4 g of a fluorine-containing compound and 16 g of a polyethyleneimine aqueous solution were added, and the mixture was heated to 75° C. and stirred for reaction for 20 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain an amphiphilic-modified inorganic composite material. Step (4), mixing the amphiphilic modified inorganic composite material, the high-performance antioxidant, and the modified polyethylene in a mass ratio of 4.8:20:100, melt blending, and film blowing to obtain a high-strength, aging-resistant PE film with a thickness of 0.5 mm, wherein the melt blending conditions are: first melt blending at 170° C. at a rotation speed of 25 r / min for 2 min, and then melt blending at a rotation speed of 60 r / min for 5 min.
[0023] Embodiment 4: This embodiment discloses a method for preparing a high-strength aging-resistant PE film, comprising the following steps: Step (1), 12 g of mercaptopropyltrimethoxysilane, 26.7 g of a 37 wt% aqueous solution of hydrochloric acid, and 216 g of ethanol were mixed, stirred at 90° C. for 25 h, and centrifuged to obtain a white precipitate, the white precipitate was dissolved in tetrahydrofuran and precipitated with 3° C. acetonitrile, filtered, washed, and dried to obtain POSS-SH; 4 g of allyl glycidyl ether, 8 g of POSS-SH, and 110 g of tetrahydrofuran were mixed and stirred at room temperature for 4 h. After the reaction was completed, the solvent and excess allyl glycidyl ether were removed by rotary evaporation at 85 ° C to obtain modified POSS; Step (2), dissolving 17.6 g of 3,5-di-tert-butyl-2-hydroxybenzaldehyde in 160 g of ethanol to obtain solution A; dissolving 9 g of p-phenylenediamine in 115 g of ethanol, and then adding 18.3 g of a 23 wt % potassium hydroxide aqueous solution to obtain solution B; adding solution B dropwise to solution A at a rate of 0.8 mL / min, reacting at 60° C. for 5 h, cooling, transferring to an ice water bath, adding 3.4 g of sodium borohydride, reacting for 2 h, and adjusting the pH to 5 with a 36 wt % hydrochloric acid aqueous solution after the reaction is completed, filtering, washing the filter residue with 50° C. hot water and toluene, and drying to obtain an intermediate product; 10 g of the intermediate product was added to 120 g of ethanol, stirred for 30 min, and then 15 g of modified POSS was added, heated to 72 ° C, and stirred for 24 h. After the reaction was completed, the solvent was evaporated to obtain a high-performance antioxidant; Step (3), pre-drying the calcium sulfate whisker at 55° C. for 2.5 h, adding the calcium sulfate whisker into a reaction vessel, heating to 100° C., adjusting the stirring speed to 1000 r / min, and then adding 3-aminopropyltriethoxysilane, continuing to stir and mix for 15 min, cooling, and obtaining surface-modified calcium sulfate whisker; wherein the mass ratio of 3-aminopropyltriethoxysilane to calcium sulfate whisker is 100:3.5; 8.6 g of surface-modified calcium sulfate whiskers, 9.5 g of glutaraldehyde, and 175 g of N,N-dimethylformamide were mixed, reacted at 100° C. for 10 h, filtered, washed, and dried to obtain graft-modified calcium sulfate whiskers; 10.5 g of 3,5-diaminobenzoic acid was dissolved in 135 g of ethanol, and 12.5 g of grafted modified calcium sulfate whiskers were added, and the mixture was stirred at 50° C. for 12 h, filtered, washed, and dried to obtain functionalized calcium sulfate whiskers; 11 g of functionalized calcium sulfate whiskers were added to 70 g of deionized water, and ultrasonically treated for 45 min. Then, 9 g of ammonium fluoride was added, and stirred at room temperature for 15 min. Then, 30 mL of a 28.6 wt% calcium chloride aqueous solution was added dropwise within 30 min. The mixture was stirred for 60 min, filtered, and the residue was washed with deionized water and ethanol, and dried at 60 ° C for 7 h to obtain an inorganic composite material. Ammonia water, deionized water and ethanol with a mass fraction of 25wt% were mixed in a volume ratio of 0.7:10:30 to obtain a mixed solution; 7.5g of the inorganic composite material was added to 51.9g of the mixed solution, and ultrasonic treatment was performed for 65min, and then 0.3g of 3-glycidyloxypropyltrimethoxysilane and 12g of ethanol were added, and the mixture was stirred and reacted at 60°C for 120min. After the reaction was completed, the mixture was filtered, washed and dried to obtain a surface-modified inorganic composite material; In a nitrogen atmosphere, add 6.5 g of perfluorooctanoyl chloride to 90 g of tetrahydrofuran, stir for 30 min, then add 1.1 g of 1,3-propylenediamine, stir and react at room temperature for 12 h, then add 15 mL of 0.04 g / mL sodium hydroxide aqueous solution, continue stirring for 50 min, filter, wash, and dry to obtain a fluorine-containing compound; 6 g of the surface-modified inorganic composite material was added to 100 g of N,N-dimethylformamide, and ultrasonically treated for 30 min. Then, 2.6 g of a fluorine-containing compound and 12 g of a polyethyleneimine aqueous solution were added, and the mixture was heated to 72° C. and stirred for reaction for 24 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain an amphiphilic-modified inorganic composite material. Step (4), mixing the amphiphilic modified inorganic composite material, the high-performance antioxidant, and the modified polyethylene in a mass ratio of 4:16:100, melt blending, and film blowing to obtain a high-strength, aging-resistant PE film with a thickness of 0.4 mm, wherein the melt blending conditions are: first melt blending at 165° C. at a rotation speed of 20 r / min for 3 min, and then melt blending at a rotation speed of 50 r / min for 6 min.
[0024] The modified polyethylene used in the above Examples 2-4 is the modified polyethylene prepared in Example 1.
[0025] Comparative Example 1: Compared with Example 4, in the process of preparing the high-strength and aging-resistant PE film, low-density polyethylene was used instead of modified polyethylene, and other conditions remained unchanged.
[0026] Comparative Example 2: Compared with Example 4, in the process of preparing the high-strength and aging-resistant PE film, the intermediate product is used to replace the high-performance antioxidant, and other conditions remain unchanged.
[0027] Comparative Example 3: Compared with Example 4, in the process of preparing the high-strength aging-resistant PE film, the high-performance antioxidant is replaced by modified POSS, and other conditions remain unchanged.
[0028] Comparative Example 4: Compared with Example 4, in the process of preparing the surface-modified calcium sulfate whiskers in Comparative Example 4, 3-glycidyloxypropyltrimethoxysilane is used instead of 3-aminopropyltriethoxysilane, and in the process of preparing the amphiphilic modified inorganic composite material, the surface-modified calcium sulfate whiskers in Comparative Example 4 are used instead of the surface-modified inorganic composite material, that is, nano-calcium fluoride is not deposited on the surface of the calcium sulfate whiskers in this comparative example, and other conditions remain unchanged.
[0029] Comparative Example 5: Compared with Example 4, in the process of preparing the high-strength and aging-resistant PE film, the surface-modified inorganic composite material is used instead of the amphiphilic modified inorganic composite material, and other conditions remain unchanged.
[0030] Comparative Example 6: Compared with Example 4, in the process of preparing the high-strength and aging-resistant PE film in Comparative Example 6, no amphiphilic modified inorganic composite material was added, and other conditions remained unchanged.
[0031] In the above embodiments and comparative examples, calcium sulfate whiskers, average diameter: 1-8 μm; average length: 30-200 μm; particle shape: rod-shaped fiber; average aspect ratio of 10-200; melting point: 1450°C, are from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; polyethyleneimine aqueous solution, concentration 25wt%, molecular weight 3000, is from Nanjing Dulai Biotechnology Co., Ltd.; low-density polyethylene (LDPE), grade LD200GH, density 0.922 g / mL, melt flow index 2.0 g / 10 min, is purchased from Sinopec Beijing Yanshan Branch.
[0032] Experimental example The performance tests were performed on the high-strength and aging-resistant PE films prepared in Examples 2-4 and Comparative Examples 1-6.
[0033] 1. Tensile strength test: The test was conducted in accordance with the international standard GB / T 13022-1991, with a test speed of 10±2mm / min, a test temperature of 23°C, and a relative humidity of 50%. The test sample was a type II dumbbell-shaped specimen, and the test was conducted using an i-Strentek 1510 electronic universal testing machine. 2. Anti-aging performance test: Each group of products was placed in an artificial accelerated aging box at 85°C for 96 hours of artificial accelerated hot air aging. After cooling to room temperature, the tensile strength after aging was measured. The anti-aging performance was measured by the retention rate of tensile strength. Tensile strength retention rate = tensile strength after aging / tensile strength before aging × 100%, Among them, the tests of tensile strength after aging and tensile strength before stretching are carried out in accordance with the international standard GB / T 13022-1991.
[0034] 3. Light transmittance test: UV-visible-near infrared spectrophotometer Cary 5000 is used for testing.
[0035] The test results are shown in Table 1: Table 1 Tensile strength / MPa Tensile strength retention rate / % Transmittance / % Example 2 64.1 99.5 92.8 Example 3 65.7 99.7 94.4 Example 4 64.9 99.6 93.5 Comparative Example 1 62.4 98.7 92.6 Comparative Example 2 61.5 96.4 93.5 Comparative Example 3 63.6 97.9 93.5 Comparative Example 4 64.0 99.3 91.0 Comparative Example 5 63.1 99.0 92.5 Comparative Example 6 60.2 98.1 89.7 It can be seen from the test results in Table 1 that the high-strength aging-resistant PE films prepared in Examples 2-4 of the present invention have excellent mechanical properties, heat-resistant aging properties, and transparency.
[0036] As can be seen from the comparison of Comparative Example 1 and Example 4, the crosslinking density of the system can be improved by modifying low-density polyethylene, the dispersibility of the amphiphilic modified inorganic composite material and the high-performance antioxidant can be improved, thereby improving the mechanical properties, heat aging resistance and transparency of the PE film; As can be seen from the comparison of Comparative Example 2 and Example 4, due to its own unique cage-shaped organic-inorganic hybrid structure, high molecular weight and high thermal stability in POSS, the mechanical properties and heat aging resistance of the PE film can be improved; As can be seen from the comparison of Comparative Example 3 and Example 4, the hindered phenol and secondary amine groups contained in the intermediate product have a positive impact on the heat aging resistance of the PE film, and the intermediate product is combined with modified POSS, the compatibility of POSS and polyethylene matrix can also be improved, and the phenolic hydroxyl group in the intermediate product can form hydrogen bonds with the modified polyethylene, thereby improving the performance of the PE film; As can be seen from the comparison of Comparative Example 4 and Example 4, the surface effect of nano calcium fluoride The compatibility of calcium sulfate whiskers and polyethylene can be improved, so that calcium sulfate whiskers can play a better effect, and the mechanical properties, heat aging resistance and transparency of the PE film are improved. The refractive index between nano calcium fluoride and polyethylene is similar, so that the PE film can maintain high transparency. From the comparison between comparative example 5 and embodiment 4, it can be seen that the introduction of hydrophobic fluorine-containing chains and hydrophilic polyethyleneimine chains in the amphiphilic modified inorganic composite material can further improve the compatibility of the inorganic composite material and polyethylene, and the amino group in the polyethyleneimine chain is combined with the epoxy resin in the modified polyethylene, which is helpful for improving the cross-linking density of the system and the dispersibility of the inorganic composite material, thereby giving the PE film excellent mechanical properties, heat aging resistance and transparency. From the comparison between comparative example 6 and embodiment 4, it can be seen that the amphiphilic modified inorganic composite material of the present invention has a significant effect on the performance of the PE film under the joint action of calcium sulfate whiskers, nano calcium fluoride, fluorine-containing chains and polyethyleneimine chains.
[0037] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-strength aging-resistant PE film, characterized in that: The following steps are involved: Step (1), preparing POSS-SH by (3-mercaptopropyl)trimethoxysilane; then modifying POSS-SH by allyl glycidyl ether to obtain modified POSS; Step (2), 3,5-di-tert-butyl-2-hydroxybenzaldehyde reacts with p-phenylenediamine to obtain an intermediate product; the intermediate product is combined with modified POSS to obtain a high-performance antioxidant; Step (3), dry-modifying the calcium sulfate whiskers with 3-aminopropyltriethoxysilane to obtain surface-modified calcium sulfate whiskers; using glutaraldehyde as a crosslinking agent, grafting 3,5-diaminobenzoic acid onto the surface-modified calcium sulfate whiskers to obtain functionalized calcium sulfate whiskers; depositing nano-calcium fluoride on the functionalized calcium sulfate whiskers to obtain an inorganic composite material; The inorganic composite material is modified by 3-glycidyloxypropyltrimethoxysilane to obtain a surface-modified inorganic composite material; Grafting fluorine-containing compounds and polyethyleneimine onto the surface-modified inorganic composite material to obtain an amphiphilic modified inorganic composite material; Step (4), mixing the amphiphilic modified inorganic composite material, the high-performance antioxidant, and the modified polyethylene, melt blending, and blowing the film to obtain a high-strength and aging-resistant PE film; The preparation method of modified polyethylene comprises the following steps: Step S1, grafting maleic anhydride onto low-density polyethylene using a solvothermal method to obtain maleic anhydride grafted polyethylene; Step S2, reacting maleic anhydride grafted polyethylene with mercaptoethylamine to obtain functionalized polyethylene; Step S3: reacting the functionalized polyethylene with 1,2-epoxy-5-hexene to obtain modified polyethylene.
2. The method for preparing a high-strength aging-resistant PE film according to claim 1, characterized in that: In the step (1), the preparation method of the modified POSS is: Mercaptopropyltrimethoxysilane, a 37wt% aqueous solution of hydrochloric acid and ethanol are mixed, stirred and reacted at 85-95°C for 20-30h, centrifuged to obtain a white precipitate, dissolved the white precipitate with tetrahydrofuran and precipitated with acetonitrile at 2-5°C, purified to obtain POSS-SH; wherein the mass ratio of mercaptopropyltrimethoxysilane, the aqueous solution of hydrochloric acid and ethanol is (8-16):(17.8-35.6):(144-288); Mix allyl glycidyl ether, POSS-SH and tetrahydrofuran, stir and react at room temperature for 3.5-4.5 hours, and purify after the reaction to obtain modified POSS; wherein the mass ratio of allyl glycidyl ether, POSS-SH and tetrahydrofuran is (3-5):(6-10):(100-120).
3. The method for preparing a high-strength aging-resistant PE film according to claim 1, characterized in that: In the step (2), the preparation method of the high performance antioxidant is: 3,5-di-tert-butyl-2-hydroxybenzaldehyde and ethanol were mixed at a mass ratio of (11.7-23.4):(120-200) The mixture is mixed in a mass ratio of (6-12):(80-150):(12.2-24.3) to obtain a solution A; p-phenylenediamine, ethanol, and a 23wt% potassium hydroxide aqueous solution are mixed in a mass ratio of (6-12):(80-150):(12.2-24.3) to obtain a solution B; the solution B is added dropwise to the solution A at a rate of 0.5-1mL / min, reacted at 55-65°C for 4.5-5.5h, cooled, transferred to an ice water bath, sodium borohydride is added, and reacted for 1.5-2.5h. After the reaction is completed, the pH is adjusted to 4.8-5.2 with a 36wt% hydrochloric acid aqueous solution, and purified to obtain an intermediate product; wherein the mass ratio of 3,5-di-tert-butyl-2-hydroxybenzaldehyde, p-phenylenediamine, and sodium borohydride is (11.7-23.4):(6-12):(2.3-4.5); The intermediate product is added to ethanol, stirred for 20-40 minutes, and then the modified POSS is added, heated to 70-75°C, and the stirring reaction is continued for 20-28 hours. After the reaction is completed, the solvent is evaporated to obtain a high-performance antioxidant; wherein the mass ratio of the intermediate product, ethanol, and modified POSS is (8-12):(100-150):(110-20).
4. The method for preparing a high-strength aging-resistant PE film according to claim 1, characterized in that: In step (3), the preparation method of the functionalized calcium sulfate whisker is: The calcium sulfate whisker is pre-dried at 50-60° C. for 2-3 hours, heated to 95-105° C., and the stirring speed is adjusted to 900-1100 r / min, and then 3-aminopropyltriethoxysilane is added, and the stirring and mixing is continued for 10-20 minutes, and cooled to obtain surface-modified calcium sulfate whisker; wherein the mass ratio of 3-aminopropyltriethoxysilane to calcium sulfate whisker is 100:(2-5); The surface-modified calcium sulfate whisker, glutaraldehyde and N,N-dimethylformamide are mixed, reacted at 95-105° C. for 9-11 hours, and purified to obtain grafted modified calcium sulfate whisker; wherein the mass ratio of the surface-modified calcium sulfate whisker, glutaraldehyde and N,N-dimethylformamide is (5.7-11.4):(6.5-12.5):(150-200); Dissolve 3,5-diaminobenzoic acid in ethanol, add grafted modified calcium sulfate whiskers, stir and react at 45-55°C for 10-14 hours, purify, and obtain functionalized calcium sulfate whiskers, wherein the mass ratio of 3,5-diaminobenzoic acid, ethanol, and grafted modified calcium sulfate whiskers is (8.5-12.5):(120-150):(10-15).
5. The method for preparing a high-strength aging-resistant PE film according to claim 1, characterized in that: In the step (3), the preparation method of the inorganic composite material is: Functionalized calcium sulfate whiskers are added to deionized water, ultrasonically treated for 30-60 minutes, and then ammonium fluoride is added. The mixture is stirred at room temperature for 10-20 minutes, and then a calcium chloride aqueous solution with a mass fraction of 28.6wt% is added dropwise within 20-40 minutes. The mixture is stirred for 50-70 minutes and purified to obtain an inorganic composite material. The dosage ratio of the functionalized calcium sulfate whiskers, deionized water, ammonium fluoride and calcium chloride aqueous solution is (10-12) g:(60-80) g:(6-12) g:(20-40) mL.
6. The method for preparing a high-strength aging-resistant PE film according to claim 1, characterized in that: In the step (3), the preparation method of the amphiphilic modified inorganic composite material is: Ammonia water, deionized water and ethanol with a mass fraction of 25wt% are mixed in a volume ratio of 0.7:10:30 to obtain a mixed solution; an inorganic composite material is added to the mixed solution, ultrasonically treated for 50-80min, and then 3-glycidyloxypropyltrimethoxysilane and ethanol are added, and stirred at 55-65°C for 100-150min. After the reaction is completed, purification is performed to obtain a surface-modified inorganic composite material; wherein the mass ratio of the mixed solution, the inorganic composite material, 3-glycidyloxypropyltrimethoxysilane and ethanol is (34.6-69.2):(5-10):(0.2-0.5):(8-16); In a nitrogen atmosphere, perfluorooctanoyl chloride is added to tetrahydrofuran, stirred for 20-40 minutes, and then 1,3-propylenediamine is added, and the reaction is stirred at room temperature for 10-15 hours, and then a sodium hydroxide aqueous solution with a concentration of 0.04 g / mL is added, and the stirring is continued for 40-60 minutes, and the fluorine-containing compound is obtained; wherein the amount ratio of perfluorooctanoyl chloride, tetrahydrofuran, 1,3-propylenediamine, and sodium hydroxide aqueous solution is (4.3-8.6) g: (80-100) g: (0.7-1.4) g: (10-20) mL; The surface modified inorganic composite material is added to N,N-dimethylformamide, ultrasonically treated for 20-40 minutes, and then a fluorine-containing compound and a polyethyleneimine aqueous solution are added, heated to 70-75°C, stirred for reaction for 20-28 hours, and after the reaction is completed, purified to obtain an amphiphilic modified inorganic composite material; wherein the mass ratio of the surface modified inorganic composite material, N,N-dimethylformamide, the fluorine-containing compound, and the polyethyleneimine aqueous solution is (5-7):(80-120):(1.8-3.4):(8-16).
7. The method for preparing a high-strength aging-resistant PE film according to claim 1, characterized in that: In the step (4), the thickness of the high-strength and aging-resistant PE film is 0.3-0.5 mm; the mass ratio of the amphiphilic modified inorganic composite material, the high-performance antioxidant, and the modified polyethylene is (3.2-4.8):(12-20):100; the melt blending conditions are: first melt blending at 160-170°C at a rotation speed of 15-25 r / min for 2-5 min, and then melt blending at a rotation speed of 40-60 r / min for 5-8 min.
8. The method for preparing a high-strength aging-resistant PE film according to claim 1, characterized in that: In the step (4), the preparation method of the modified polyethylene is: Step S1, mixing low-density polyethylene, maleic anhydride, dicumyl peroxide, and toluene, heating to 140-160° C. and maintaining for 4.5-5.5 hours in a sealed environment, naturally cooling to room temperature, and purifying to obtain maleic anhydride-grafted polyethylene; wherein the mass ratio of low-density polyethylene, maleic anhydride, dicumyl peroxide, and toluene is (5-10):(0.5-1.2):(0.4-0.6):(40-60); Step S2, in a nitrogen atmosphere, adding maleic anhydride grafted polyethylene to N,N-dimethylformamide, stirring for 20-40 minutes, then adding mercaptoethylamine, reacting at 55-65° C. in a nitrogen atmosphere for 5.5-6.5 hours, purifying, and obtaining functionalized polyethylene; wherein the mass ratio of maleic anhydride grafted polyethylene, N,N-dimethylformamide, and mercaptoethylamine is (6-10):(80-100):(0.8-1.2); Step S3, adding the functionalized polyethylene to N,N-dimethylformamide, stirring for 20-40 minutes, then adding 1,2-epoxy-5-hexene, stirring and reacting at room temperature for 5-7 hours, purifying, and obtaining modified polyethylene; wherein the mass ratio of the functionalized polyethylene, N,N-dimethylformamide, and 1,2-epoxy-5-hexene is (6-10):(80-100):(1.1-1.8).
9. A high-strength aging-resistant PE film prepared by the method for preparing a high-strength aging-resistant PE film according to any one of claims 1 to 8.
10. Use of the high-strength and aging-resistant PE film according to claim 9 in UV-cured hose inner membrane materials.
Citation Information
Patent Citations
Mildew-proof and anti-skid TPE (thermoplastic elastomer) material as well as preparation method and application thereof in preparation of toothbrush handle
CN118515947A
Cited By
Composite current collector base film and preparation method thereof
CN121991387A